Lembaga Harta Bersama Dalam Masyarakat Bilateral Perpektif Hukum Islam - Saifullah Masduki (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
This paper is to study joint property (harta bersama) from the genealogy perpective with it’s locus to bilateral genealogy as in Java, Sunda and Aceh society. Bilateral system of genealogy choosed in this paper, because a unilateral genealogy (patrilineal and matrilineal), will be marginalized along with the development of era and will be subtituded with bilateral genealogy. In addition, this paper also pretend to see how Islamica law to be adaptive to the customory law as a living law, especially in matter of the law of marital property. Basically, this study is characterized as a secondary study or study of the law in books, that is the review of jurist manuscript and documentation about the norms that regulates law interaction in society from the status aspect. On of the conclusions of this paper is although the marital property law is not mentioned in Islamic law, but if we see the disired genealogy or kinship system which led to the bilateral system, then we are sure that Islamic law will adaptively absorb the community property as exist in customory law of bilateral system.